Synthesis of biofilm filled with PLA and Chlorella algae / Muhammad Faiz Fadzel - Fadzel, Muhammad Faiz (2023)
The public is becoming more and more interested in ecologically friendly packaging options, with biodegradable plastic being one of the numerous solutions. Because it offers a biodegradable alternative to numerous items, PLA was chosen in this investigation. PLA's brittleness and slow rate of degradation, however, restrict its usage. To save expenses and speed up deterioration, chlorella algae are utilised as fillers. This study investigated the adhesion potential of biofilm composites between PLA and Chlorella and characterised the FTIR and moisture content, respectively. Making PLA/Alga composites using the solvent casting technique is the most efficient method.